Os vereadores e o ofício da política em Riachuelo: recursos sociais, redes de relações e dominação - Bomfim, Fagner dos Santos (2019)
This work has as main objective to analyze the social resource's (professional, academic, institutional, politic, kinship, domination, etc.) that are fundamental to structurate the politic as an occcupation, and as well, apprehend the abillities that are valued for the constitution and maintenence of a career as a politic professional. Therefore, this is a study about the principles of a professional group, that is defined especially, by the process of construction of a professional career, which is integrated with the electoral resource of vote. The universe of analysis consists in a group of political actors - the city councilors from the 2016's campaing - which are active in the politics of the country of Riachuelo from Sergipe's state, and are constitued as significant structures of autorithy, as well, they participate in the distribution of social resources for a political consecration into a local and regional level. In terms of methodology, some techniques were fundamental for the caption of the biographies of those actors, which mean the use of questionnaires, direct interviews with the city councilors, the employees from the Chamber of Councilors and political advisors, and also the use of participant observations and field journal. However, the historical construction of politics in Riachuelo stimulated the utilization of the concept of "kinship" (LEWIN, 1993; QUEIROZ, 1976), which allowed to apprehend the central role that is interpretated by the social ties and the systems of aliances and the dynamics of integration and reintegration of leading groups. Those types of social ties are understood as a social resource which was used in the begining of local political history as a strategy to create and integrate a network of aliances of leading groups. Therefore, the visualization of those social networks into the construction of a professional political career of a city councilor, allowed to comprehend how it is related to the use of different resources and types of domination into the politics from Riachuelo.